Obtención de bioplástico a partir de la extracción de almidón de los residuos de papa capiro (2022)
The main objective of this degree work was based on obtaining a bioplastic at the laboratory level from the extraction of starch from Papa Capiro residues. Therefore, the research was divided into four objectives; Characterization of the raw material, extraction of starch, elaboration of the bioplastic and finally the biodegradability of the bioplastic. The raw material was characterized and the pH, moisture percentage and starch percentage were determined. In which the samples varied between a pH of 5.72 - 6.45 showing acid results on the pH scale, the percentage of humidity was also obtained between 15.98 - 17.7% and finally the percentage of starch between 16.22 - 17.98%. These data helped us to validate the quality of potato starch that has been obtained since it was compared with bibliographic references of potato starches that are in perfect condition.